Ekonomi Berkelanjutan : Solusi untuk Meningkatkan Ekonomi Masyarakat dan Perbankan di Indonesia - Siti Wildatul Musyarrofah; M. Zidny Nafi’ Hasbi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the impact of Mekar Bank loans on the economic well-being of clients and the implementation of sustainable economic principles in financing. The method used is a qualitative approach with case studies conducted in several regions of Indonesia, particularly in the researcher's village, Blimbing, Kesambi, Besuki, Situbondo, where the program is implemented. The results of this study show that Mekar Bank loans have provided easier access to financing aligned with sustainable economic principles, contributing to increased income and improved living standards, especially among women. However, the study also identifies several challenges in the program's implementation, including a lack of client understanding regarding sustainable economic principles and effective financial management. To enhance the program's effectiveness, additional education on sustainable principles and financial management is necessary. Thus, Mekar Bank loans serve not only as a financing tool but also as a means of economic empowerment. These loans also encourage clients to adopt more sustainable business practices, such as the use of sustainable business capital. Therefore, Mekar Bank loans help promote economic growth while also fostering sustainable economic development, ensuring that the positive impacts of these loans continue and extend to more segments of society.